Relationship among thermal environment, stage of lactation, body characteristics, yield and milk constituents of dairy Gyr cows managed on pasture - De-Sousa, Karolini Tenffen (2024)
Our aims were to evaluate changes in body characteristics, milk yield and milk constituents as well as to determine the relationship between the thermal environment and production characteristics during the first lactation of dairy Gyr cows managed on pasture. Between 2013 and 2015, forty-five primiparous dairy Gyr cows were evaluated from prepartum to 10 months of lactation in Southeast of Brazil. Body weight, body condition score (BCS), subcutaneous fat thickness (SFT), milk yield (305 d), and milk constituents were collected monthly and progesterone was collected weekly. Additionally, we determined the temperature humidity index (THI) based on microclimate data. Overall, the cows lost body weight until six months of lactation and there was a progressive decrease in BCS, SFT, milk yield and milk lactose as the months in lactation progressed. In contrast, there was an increase in milk fat, milk protein and milk solids. The thermal environment did not pose a consistent heat challenge, nevertheless, we found a positive correlation between the average THI two days before milk collection with milk yield, fat and lactose contents, but in contrast a negative correlation was found with total solids and protein. In conclusion, the THI and months of lactation affected the yield and constituents of milk. However, more studies are necessary to understand the impacts of body characteristics and thermal environment on yield and milk constituents throughout the productive life of Gyr dairy cows.